Unholy trinity : the IMF, World Bank and WTO - Peet, Richard (Malaysia ; SIRD, London ; New York : Zed Books, 2003)
Who really runs the global economy? Who benefits most from it? The answer is a triad of 'governance institutions' - The IMF, the World Bank and the WTO. This book argues that neoliberal global capitalism has entered a period of crisis so severe that governance will become impossible.
Includes bibliographical references (p. [227]-239) and index.
oif 13/02/16
Loans
Keywords: International Monetary Fund; World Bank; World Trade Organization; Globalization